2004
DOI: 10.1177/000348940411300605
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Mediated Disorders Associated with Idiopathic Sudden Sensorineural Hearing Loss

Abstract: Different immune disorders are involved in the development of sudden sensorineural hearing loss (SSNHL). This includes a wide spectrum of immune-mediated disorders such as immune complexes, production of autoantibodies to the inner ear proteins, production of anticardiolipin (aCL) antibodies, and cellular immune defects. Some studies have also found an elevation of total IgE levels and a type 1 immune reaction. Our objective was to establish the association of "idiopathic" SSNHL (ISSNHL) with various autoantib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 30 publications
3
61
0
3
Order By: Relevance
“…In addition to the above findings, our study indicates elevation of ANA (25.4%) in SSNHL patients with a prevalence greater than that seen in a normal patient population. The prevalence of ANA in patients with SSNHL has been studied and 17-43% of the patients have been reported to be ANA positive [Toubi et al, 2004;Ottaviani et al, 1999;Agrup and Luxon, 2006]. We confirmed the reported association of these autoantibodies with SSNHL, thereby further supporting the assumption that SSNHL is partially immune-mediated [Toubi et al, 2004].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition to the above findings, our study indicates elevation of ANA (25.4%) in SSNHL patients with a prevalence greater than that seen in a normal patient population. The prevalence of ANA in patients with SSNHL has been studied and 17-43% of the patients have been reported to be ANA positive [Toubi et al, 2004;Ottaviani et al, 1999;Agrup and Luxon, 2006]. We confirmed the reported association of these autoantibodies with SSNHL, thereby further supporting the assumption that SSNHL is partially immune-mediated [Toubi et al, 2004].…”
Section: Discussionsupporting
confidence: 84%
“…These autoantibodies have been suggested as inducing thrombosis of the labyrinthine vessels with subsequent damage of the inner ear resulting in SSNHL [Hisashi et al, 1993]. Anti-CL and anti-␤ 2 GP1 antibodies have been reported to occur in 12.9-31% and 6.6-12% of patients with SSNHL, respectively [Marcucci et al, 2005;Bachor et al, 2005;Toubi et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Merchant et al [4] studied the temporal bone histopathology of 15 deaf ears and found viral particles without microscopy; thus, no direct cochlear evidence has been found for viral infection. No immune- or autoimmune-mediated injuries have been reported [10], indicating a lack of support for possible immune etiologies. The thrombosis hypothesis regarding the pathogenesis of SSNHL should be questioned because there was no difference in incidence rate between males and females [11].…”
Section: Discussionmentioning
confidence: 99%
“…According to the viral theory, ISSNHL is due to a herpes simplex virus infection; however, no specific serological profiles or response to antiviral treatment has been reported [2]. An immune-mediated hypothesis also cannot explain why impaired immunity and autoimmune causes are not observed in every case [13]. The data are given as the means ± standard deviation or numbers and percentages; < 0.05 value was accepted as significant level and the significant differences between the groups were shown in bold.…”
Section: Discussionmentioning
confidence: 99%